Faculty of Hotel & Tourism Management nutrition education and healthy menu planning in enhancing healthy eating environments at kindergarten / Mohamad Hasril Abu Bakar & Nurul Hidayah Mohd Sha’ari - Abu Bakar, Mohamad Hasril; Mohd Sha’ari, Nurul Hidayah (2017)
Children are asset to the nation. To ensure the health of children it starts with good nutrition and menu planning. Nutrition education play and important matter and part of the curriculum that can be developed in our community through an educational institution. It is important to educate people about nutrition to prevent chronic disease from a young age. Therefore, this study aimed three objectives which are to identify the importance of good nutrition practices at kindergarten, to identify nutrition education practice at kindergarten and to explore healthy menu planning practice at kindergarten. The result shows that different educational tools have different ways to educated children. Same goes to healthy menu planning at kindergarten worldwide, different countries have a different procedure in menu planning. The new findings and ideas consequently can be proposed and added to nutrition education and healthy menu planning in Malaysia and worldwide globally. This eventually hopes may help to improve the healthy eating environment at kindergarten and preventing chronic disease among children. Nevertheless, this study is the preliminary study that covers the surface info of the respective objective and some info maybe not enough to cover worldwide information due to time constraint etc. However, the findings explored and discuss is hoping can give a new contribution to the knowledge that may help society especially foodservice management industries to develop more opportunity to serve the best for healthy eating environment at kindergarten institution.